Presentation for Global Food 50/50 Launch Event - Tanaka, Sonja; Njuki, Jemimah (2024)
The Global Food 50/50 initiative monitors progress and holds food system organizations accountable for advancing gender-just and equitable food systems. This event marks the launch of the third annual Global Food 50/50 Report, which reviews the gender- and equity-related policies and practices of 51 global food system organizations to assess two interlinked dimensions of inequality: inequality of opportunity in careers within organizations and inequality in who benefits from the global food system.